PENGARUH PUTARAN SPINDLE SPEED TERHADAP KEAUSAN PAHAT CARBIDE PADA PROSES PEMBUBUTAN BAJA ST37 - Ratlalan, Roberth M.; Valentine, Odilia (Otopro, 2024)
The machining process has an important interaction between the tool and the workpiece, in which case the workpiece experiences intersection and the tool experiences friction. This friction occurs when the chisel touches the flowing surface and touches the area where the surface of the workpiece has crossed. As a result of friction, the tool wears out. Wear and tear that occurs is caused by expansion or enlargement to a specified limit, resulting in it not being used or having no function because damage has occurred. The research variables used three chisel bits and three specimens which were used to test their wear at 450 rpm, 1200 rpm and 2200 rpm rotation using a portable LCD digital microscope. Following are the results of the chisel bit research showing the wear of carbide bits using 3 specimens, so the wear value for the first tool was 3.09 µm, the second tool was 2.26 µm, and the third tool was 11.36 µm.